Intergenotypic competition in soybean - Bisognin, Dilson Antonio; Vernetti, Francisco de Jesus; Gastel, Mário Franklin da Cunha; Zonta, Élio Paulo (Pesquisa Agropecuaria Brasileira, 1995)
The effect of intergenotypic competition and of the genotypic frequency on soybean (Glycine max) cultivars; blends was evaluated through an experiment carried out along the 1989/90 crop season, in Capão do Leão county, RS, Brazil. Five cultivars, IAS 5, Ivorá, Bragg, Ivaí and BR 8 - Pelotas in pure stands, and the blends of Bragg with every cultivar, in five different proportions, were allocated to a partially balanced 5 x 5 lattice design, with four replicates. Among the four blends compared, Bragg + IAS 5 and Bragg + BR 8 - Pelotas showed significant yield differences, according to the genotypic frequencies. Yield gains of the blends IAS 5 + Bragg and BR 8 - Pelotas + Bragg, in relation to the components mean, were 9.04 and 8.59%; in relation to the best component yield they were 8.49 and -0.85%, respectively. The highest yield of the blend BR 8 - Pelotas + Bragg was; 9.7% higher than the yield of IAS 5 + Bragg, although it had shown smaller efficiency of the response to the effects of intergenotypic competition. The intergenotypic competition may be explored in soybean breeding, aiming to obtain cultivar blends with superior yield and performance, and different reponses to intergenotypic competition are observed in distinct cultivar blends and proportions.